2017
DOI: 10.3389/fnbeh.2017.00166
|View full text |Cite
|
Sign up to set email alerts
|

Theta Oscillations Related to Orientation Recognition in Unattended Condition: A vMMN Study

Abstract: Orientation is one of the important elements of objects that can influence visual processing. In this study, we examined whether changes in orientation could be detected automatically under unattended condition. Visual mismatch negativity (vMMN) was used to analyze this processing. In addition, we investigated the underlying neural oscillatory activity. Non-phase-locked spectral power was used to explore the specific frequency related to unexpected changes in orientation. The experiment consisted of standard (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 21 publications
3
19
0
Order By: Relevance
“…In this study, we found significant complexity differences among four groups on multiple temporal scales, especially on longer time scales, due to MSE’s capability to average out short time scale fluctuations ( Smith et al, 2014 ; Yan et al, 2017 ). Thus, compared with SE, researchers performed MSE for complexity analysis obtained richer and more comprehensive information in aging and neurodegenerative diseases ( Humeauheurtier, 2016 ; Shang, 2017 ).…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…In this study, we found significant complexity differences among four groups on multiple temporal scales, especially on longer time scales, due to MSE’s capability to average out short time scale fluctuations ( Smith et al, 2014 ; Yan et al, 2017 ). Thus, compared with SE, researchers performed MSE for complexity analysis obtained richer and more comprehensive information in aging and neurodegenerative diseases ( Humeauheurtier, 2016 ; Shang, 2017 ).…”
Section: Discussionmentioning
confidence: 68%
“…As the most complex organ of the human body, the human brain regulates multifaceted actions with billions of neurons and synapses ( Fox et al, 2007 ). Therefore, the BOLD signals possess complex temporal fluctuations, which could be imitated by nonlinear dynamical processes ( Soltysik et al, 2004 ; Stephan et al, 2008 ; Yan et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Concerning the functional meaning of these low-frequency bands (EEG alpha, delta, and theta), depending on the setting, paradigm, task and stimuli, an increase of amplitude in these bands may index either cortical activation or inhibition. During engagement of the participant in perceptual tasks, an increase of slow band amplitude was associated with better performance ( Henry et al, 2014 ; Arnal et al, 2015 ; Yan et al, 2017 ). The same EEG bands have been studied and modeled as biomarkers of optimal performance in sport (for a review, see Cheron et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…Hence, the conclusions must be further confirmed with a larger sample size. In the future, we will design different experiments related to neurocognitive function ( 43 , 44 ) and use various analytical methods to explore the pathologic mechanisms of neurocognitive deficits in patients.…”
Section: Discussionmentioning
confidence: 99%